SEBARAN KOMODITAS TERNAK UNGGULAN DI JAWA DAN LUAR JAWA IMPLIKASINYA BAGI PERDAGANGAN TERNAK - RACHMAT HENDAYANA (SOCA: Jurnal Sosial Ekonomi Pertanian, 2005)
The superior livestock commodity owns strategic position to be developed inregion base on technical (land and climate conditions), socio economics, and institutionsconsideration. This research aim to discuss superior livestock commodity in Java and offJava and also the implication for livestock trading. Discussion conducted base onsecondary data provided by CBS (Central Bureau of Statistics) for five year period (1997- 2001). Location Quotient ( LQ) approach uses for data analysis and result shows: ( a)The performance of livestock population for ruminant and non ruminant in everyprovince either in Java and Off Java shows variative, ( b) With LQ approach known thatregion of province have potential selected superior livestock type to be commercialized.In this case province owning superior livestock shown by value of LQ which was highrelative (> 1), (c) Potential gap of livestock population in every province push thehappening of interisland livestock trading either in Java and Off Java.